Cold-related injuries in a cohort of homeless adults. Issue 1 (2nd January 2019) - Zhang, Paige; Bassil, Kate; Gower, Stephanie; Katic, Marko; Kiss, Alex; Gogosis, Evie; Hwang, Stephen W.
ABSTRACT: People experiencing homelessness have an increased risk of cold-related injuries. This study determined the rate of emergency department (ED) visits for cold-related injuries among homeless adults and low-income controls in Toronto, Canada. Homeless individuals were recruited at shelters and meal programs. Age- and sex-matched controls living in low-income neighborhoods were selected. ED utilization was ascertained over 4-years of follow-up (2005–9) using administrative databases. A total of 16 ED visits for cold-related injuries were observed among 587 homeless men and 296 homeless women. The rate of ED visits was 6.7 (95% CI, 4.2–12.4) per 1000 person-years of observation among homeless men and 0.9 (95% CI, 0.03–5.6) among homeless women. ED visit rates were significantly higher among homeless men compared to low-income men ( P  < 0.001) and significantly higher among homeless men compared to homeless women ( P  = 0.03). Targeted public health interventions are needed to reduce the risk of cold-related injuries among people experiencing homelessness.